The effect of UV – Radiation on Thermal and Mechanical Properties of (PP/LDPE) Blends - Balkees M. Aldabbagh; Hanaa J. Al shimary; Adnan R. Ahmmed (Tikrit Journal of Pure Science, 2023)
UV-rad effected on thermal and mechanical properties (density, Shore D hardness, melt flow index, DSC) properties were studied for polypropylene (PP) blended with low density polyethylene (LDPE) at different ratios (10% PP+90% LDPE), (25%PP+75%LDPE). Results shows decreasing of blend density with increasing of  PP content and increasing  of it  after UV-RAD for (15 hr.), also Shore D hardness decreased at the first ratio of  PP (10%) then it increased with increasing of PP contain. Also Shore D increases after UV rad for (15 hr.). Melt flow index (MFI) decreased after UV rad, also the UV rad leads to increasing of crystallinity regions of blends.